The relationship between professional commitment, spiritual well-being, and medication errors among iranian nurses - Rahim Baghaei; Mohammad Yousefi Asl; Rozita Cheraghi; Hamidreza Khalkhali; Roya Naderi (Kashan University of Medical Sciences, 2022)
Background: Medication errors (MEs) threaten patient safety and can lead to patient death. Some studies have shown the relationship between spirituality and professional commitment, but no study has been conducted on the relationship between nurses' professional commitment, spiritual well-being, and MEs. Objectives: This study aimed to examine the relationship between nurses' professional commitment, spiritual well-being, and MEs. Methods: This cross-sectional study was conducted in 2018 on 326 nurses working in educational hospitals of Urmia University of Medical Sciences, Urmia, Iran. Data were collected using four questionnaires, including a demographic data form, a researcher-made self-report questionnaire about nurses' MEs, the Palutzian and Ellison Spiritual Well-being Questionnaire, and the Nurses' Professional Commitment Scale. The Pearson correlation coefficient, independent samples t-test, analysis of variance, and regression analysis were used to analyze the data. Results: The mean ME in the past 3 months was 1.1 ± 1.64. The mean professional commitment and spiritual well-being were also 30.67 ± 7.6 and 56.99 ± 13.8, respectively. Significant correlations were found between spiritual well-being and MEs (r = −0.32, P < 0.001), but no significant correlation was found between professional commitment and MEs (r = 0.035, P = 0.52). However, a significant correlation was observed between professional commitment and spiritual well-being (r = 0.3, P < 0.001). Conclusion: Higher professional commitment among nurses would enhance their spiritual well-being and reduce MEs. Professional commitment may promote spiritual well-being, resulting in fewer MEs as an indirect effect.